Helping themselves and helping others: how the passage of time influences why mothers with addictions take part in research - Crawford, Karen; Russell, Lynda; Graham, Sharon; Turner, Fiona (Frontiers in Psychiatry, 2023)
Introduction Women with addiction issues are under-researched, despite previous evidence that women’s needs are less understood than men’s and that services can overlook gender-specific issues. The majority of women in treatment are mothers and a significant number have contact with child welfare services. The voices of these women are needed to shape and influence evidence-based treatment and service development. Aim To examine reasons and rationale for participation in research in mothers with addiction issues and involvement with the child welfare system. Method Reflexive thematic analysis was used on interview transcripts from two qualitative studies. Individual themes from each study were combined and analysed to develop themes covering both studies and at different timepoints in process of child welfare assessment or removal of child/ren. Results Three themes were identified (1) altruism; (2) personal benefit; and (3) empowerment. These mothers wanted to help with research. However, they also participated with the hope that this might facilitate the return of their children or help them to access support or services. A change over time was evident and, in those further down the line from child removal, there was a stronger want for their voices to be heard in order to advocate for other women and create change in services.